Analisis Pengaruh Moment Gyroscope Pada Keseimbangan Pendulum Cartessian - Muhammad Iqbal Nugraha; J Hartati; W Afridani; Masdani Masdani (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Crane is identical to the pendulum in term of its control mechanism. Based on modelling, these two devices are very similar and therefore, the pendulum can be used as a prototype for controlling a crane. This research aims to control the balance or to reduce the swing on the pendulum by utilizing the moment of gyroscope with a mass pendulum up to 1.5 kg. Gyroscope was designed and made in the form of a disc, in which dimensions and materials used were determined according to the desired moment force. The PID controller was used to control the speed of gyroscope based on the angle of the pendulum (?). Based on the results of the experiment, it was obtained that the resulting settling time was 2.29 times faster than without control in average. The overshoot and rise time resulted by the system using gyroscope were very similar to the system which is without gyroscope. However, the steady state error was totally eliminated. It can be concluded that the moment of gyroscope is able to be used for controlling the pendulum or crane.